Self-Reported General and Oral Health in Adults in the United States: NHANES 1999-2014 - Li KY; Okunseri CE; McGrath C; Wong MCM (Dove Medical Press, 2019)
Kar Yan Li,1 Christopher E Okunseri,2 Colman McGrath,3 May CM Wong3 1Faculty of Dentistry, The University of Hong Kong, Hong Kong, People’s Republic of China; 2Department of Clinical Services, School of Dentistry, Marquette University, Milwaukee, WI, USA; 3Dental Public Health, Faculty of Dentistry, The University of Hong Kong, Hong Kong, People’s Republic of ChinaCorrespondence: May CM WongDental Public Health, Faculty of Dentistry, The University of Hong Kong, 34 Hospital Road, Hong Kong, People’s Republic of ChinaTel +852-2859-0422Fax +852-2858-7874Email mcmwong@hku.hkObjective: To assess self-reported general health (SRGH) and self-reported oral health (SROH), and to identify factors associated with these self-health reports among adults in the United States.Methods: Data from the National Health and Nutrition Examination Survey (NHANES) for 1999 to 2014 were analyzed. Survey-weighted descriptive statistics were computed and Pearson correlations between the two self-reported health status measures were tested. Separate multivariable logistic regressions in SROH and SRGH were performed. Measures of inequality-absolute inequality (AI) and relative inequality (RI) in SRGH and SROH were investigated.Results: The sample consisted of 37,904 adults. Survey-weighted proportions of “excellent or very good” general health decreased from 54% in 1999–2000 to 45% in 2013–2014 and that of oral health increased from 27% in 1999–2000 to 38% in 2013–2014. Whites, participants with college degrees and those ≥400% of family poverty income ratio (PIR) had a higher probability of reporting “excellent or very good” general and oral health. Young people had a higher probability of reporting “excellent or very good” general health and the probability of reporting “excellent or very good” oral health fluctuated among the different age groups. There was a slight increase in both AI and RI by sociodemographic factors for SRGH (except for gender). For SROH, AI increased slightly, and RI decreased slightly (except for education) over the same period.Conclusion: Self-reported general health had higher ratings than self-reported oral health. Survey period, age, race/ethnicity, education and family PIR were significantly associated with SRGH and SROH, but gender was only significant in the SROH model. SRGH was significantly associated with SROH after adjusting for other sociodemographic factors.Keywords: adults, epidemiology, oral health, public health